Structural characterization of Li-MN doped powders prepared by Pechini's method - Cavalheiro, A. A. [UNESP]; Zaghete, M. A. [UNESP]; Paiva-Santos, C. O. [UNESP]; Silva Giotto, M. T. [UNESP]; Cilense, M. [UNESP]; Varela, José Arana [UNESP]; Mascarenhas, Y. P. (Trans Tech Publications Ltd, 2001)
Pechini's method has been successfully used to prepare Li-doped MgNb2O6(MN) at short time and low temperature. It consists in the preparation of metal citrate solution, which is polymerized at 250°C to form a high viscous resin. This resin was burned in a box type furnace at 400°C/2h and ground in a mortar. Successive steps of calcination up to 900°C were used to form a crystalline precursor. SEM, DTA and XRD were used to characterize the powders. MN precursor powders containing from 0.1 to 5.0 mol% of LiNbO3 additive was prepared aiming better dielectric properties and microstructural characteristics of the PMN prepared from columbite route. SEM analysis showed that particles increased by sintering, forming large agglomerates. The surface area is also substantially reduced with the increase in additive amount above 1.0 mol%. In XRD pattern of the precursor material with 5.0 mol% of additive was observed the LiNbO3 phase of trigonal structure. XRD data were used for Rietveld refinement and a decrease in microstrain and pronounced increase in crystallite size with the increase of LiNbO3 were observed. It is in agreement with the particle morphologies observed by SEM analysis.
Keywords: Calcination; Crystal microstructure; Dielectric properties of solids; Differential thermal analysis; Doping (additives); Lithium; Polymerization; Resins; Scanning electron microscopy; Sintering; Surface structure; X ray diffraction analysis; Columbite; Lead magnesium niobate; Magnesium niobate; Pechinis method; Rietveld refinement; Surface area; Magnesium compounds